ANALYSIS OF E-COMMERCE MARKETPLACES IN UZBEKISTAN: THE CASE OF UZUM MARKET, ZOODMALL, AND ALIFSHOP - Sulaymonova Adiba Baxodirjonovna (Ecominds Press, 2025)
This article provides a comparative analysis of the leading and developing e-commerce marketplaces in Uzbekistan — Uzum Market, ZoodMall, and Alifshop — in the context of the country’s rapidly evolving digital economy. Drawing on recent market data and peer-reviewed sources, the study explores each platform’s business model, technological integration, and strategic positioning. Uzum Market is identified as a domestic ecosystem leader with a fintech foundation, ZoodMall as a cross-border marketplace emphasizing digital credit services, and Alifshop as a values-based, Sharia-compliant platform. The article also examines the broader trends of fintech integration, BNPL services, and digital consumer behavior in Uzbekistan. Findings offer relevant insights for policymakers, digital strategists, and investors involved in Central Asia’s online commerce sector.
Keywords: Uzbekistan; e-commerce; Uzum Market; ZoodMall; Alifshop; fintech; BNPL; marketplace platform; digital economy; business model; online retail; comparative analysis.